2015
DOI: 10.3390/sym7010125
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography and Magnetic Phenomena

Abstract: This essay describes the development of groups used for the specification of symmetries from ordinary and magnetic point groups to Fedorov and magnetic space groups, as well as other varieties of groups useful in the study of symmetric objects. In particular, we consider the problem of some incorrectness in Vol. A of the International Tables for Crystallography. Some results of tensor calculus are presented in connection with magnetoelectric phenomena, where we demonstrate the use of Ascher's trinities and Ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The magnetic point group of the normal state is O h ⊗ {1, T }, where T denotes time reversal. Since {1, T } appears as a factor group, the magnetic point group is "gray" [33,34]. The Hermann-Mauguin notation is m 3m1 , where 1 stands for time reversal combined with the spatial identity operation [33].…”
Section: Model Systemmentioning
confidence: 99%
“…The magnetic point group of the normal state is O h ⊗ {1, T }, where T denotes time reversal. Since {1, T } appears as a factor group, the magnetic point group is "gray" [33,34]. The Hermann-Mauguin notation is m 3m1 , where 1 stands for time reversal combined with the spatial identity operation [33].…”
Section: Model Systemmentioning
confidence: 99%
“…While the significance of raising T N by nearly 75 K via delithiation can be readily appreciated, the relevance of also changing the magnetic point symmetry may not be immediately apparent. The magnetic point group for a material has implications for the type of allowed magnetic properties. In the case of the olivine phosphates, it is the magnetoelectric properties that are of primary importance to us. ,,,, Mercier demonstrated that all the olivines for M = Mn, Fe, Co, and Ni display magnetoelectric properties whereby the magnetization is related to an externally applied electric field E via the magnetoelectric tensor α (given by ) . Furthermore, LiCoPO 4 was found to display a special type of magnetoelectricity known as ferrotoroidicity. , This latter property completes the table of the three known primary ferroicsferromagnetism, ferroelectricity, and ferroelasticity (Figure b–d). The fourth ferroic, ferrotoroidicity (Figure a), is the result of toroidal moments ordering spontaneously upon cooling below a certain temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For more details and forms of tensors, we refer to the reviews in Refs. [15,[20][21][22], and the original works in Refs. [16,18,19,23,24].…”
Section: Introductionmentioning
confidence: 99%